Synthetic Phonics on the Development of Reading Aloud - Reka Roefika Novita Putri; Zaitun Hateem (Universitas Muhammadiyah Jember, 2020)
This study aims to know the effect of synthetic phonics on the development of students reading aloud skills. This study was conducted at State Junior High School 3 Babelan, Bekasi, Indonesia. This study used a quantitative method, true-research experimental design with one group pre-test and post-test. The population of this research is all 8th grade students, and for two classes of 8th grade were taken as the sample, where one class is experimental and the other is control with the total number of 72 participants. A pre-test and post-test were given to know whether synthetic phonics is effective. The obtained result of both tests from the two classes were compared. The findings showed that the lowest score in the experimental class was 71 while the highest was 89. Meanwhile, the lowest and the highest score of control class were 62 and 75, respectively. The difference of the highest scores between that obtained in the experimental and that in the control class is 14, meaning that experimental class gained 14 scores. It can be concluded that synthetic phonics is effective in the development of students’ reading aloud skills, this study recommends continuation using synthetic phonics to develop students’ reading aloud skills.